Saccharomyces cerevisiae BY4741 and W303-1A laboratory strains differ in salt tolerance - Petrezselyova, Silvia; Zahradka, Jaromir; Sychrova, Hana (Fungal biology, 2010)
Saccharomyces cerevisiae yeast cells serve as a model to elucidate the bases of salt tolerance and potassium homeostasis regulation in eukaryotic cells. In this study, we show that two widely used laboratory strains, BY4741 and W303-1A, differ not only in cell size and volume but also in their relative plasma-membrane potential (estimated with a potentiometric fluorescent dye diS-C3(3) and as Hygromycin B sensitivity) and tolerance to alkali-metal cations. W303-1A cells and their mutant derivatives lacking either uptake (trk1 trk2) or efflux (nha1) systems for alkali-metal cations are more tolerant to toxic sodium and lithium cations but also more sensitive to higher external concentrations of potassium than BY4741 cells and their mutants. Moreover, our results suggest that though the two strains do not differ in the total potassium content, the regulation of intracellular potassium homeostasis is probably not the same in BY4741 and W303-1A cells.
Keywords: buněčná membrána; kationty; Sodium; draslík; Lithium; druhová specificita; lithium; Potassium; Saccharomyces cerevisiae - proteiny; hygromycin B; mutace; Cations; Gene Expression Regulation, Fungal; Saccharomyces cerevisiae Proteins; Salt Tolerance; biologický transport; homeostáza; Homeostasis; sodík; Species Specificity; Saccharomyces cerevisiae; tolerance k soli; Cell Membrane; Membrane Potentials; Hygromycin B; Mutation; membránové potenciály; regulace genové exprese u hub; Biological Transport